Modular integration of a matrix converter. Issue 1 (January 2016) - Solomon, Adane Kassa; Skuriat, Robert; Castellazzi, Alberto; Wheeler, Pat
Abstract : The future development of high‐performance power electronics will rely increasingly on system‐level integration, where semiconductor devices are co‐packaged with other active and passive components (e.g., gate drivers, filter capacitors, and inductors) into a power module. In view of the widespread electrification of pivotal elements of the energy generation and distribution infrastructure (e.g., smart grids, electric aircraft, electric vehicles), modularity is also increasingly gaining importance as a means of enhancing overall system performance and reducing long‐term maintenance costs. This paper focuses on the development of a highly integrated three‐to‐one phase matrix converter for avionic applications. It proposes an integration approach that enhances the volumetric and gravimetric power handling capability, with enhanced electromagnetic and electrothermal performance as compared to established solutions. Maintenance is also simplified by the modular assembly approach. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.